Resilience of Natural Disaster Victims Based on Social Capital Community Recovery Strategy for Flash Floods in Ladang Rimba - Hariani, Riri Rezeki; Arisuma, Neri; Saleh, Arifin (Jurnal Penelitian Medan Agama, 2024)
Flooding is a natural phenomenon caused in areas where many rivers flow. This research intends to describe, analyze and reveal the flash flood disaster in Ladang Rimba in 2023. In its development, this method uses environmental history by utilizing sources obtained, both written and oral, which are related to the topic of discussion. The results of this research show that after the 2023 Ladang Rimba flash flood disaster, it was a sad story for all the people living in the flood area. Severe damage due to flash floods in Gampong Ladang Rimba in Central Trumon District still leaves mud sediment with a thickness of up to 120 cm. still covering residential areas, residents' houses and various infrastructure. The impacts of flash floods in Ladang Rimba include: experiencing levels of damage to infrastructure, including housing, roads, bridges and utilities, loss of livelihoods, business closures, and impacts on local industry, social and psychological impacts on individuals and communities, including trauma, problems mental health, and community cohesion, the level of community involvement in the recovery process and empowerment of local residents. For this reason, a comprehensive review is needed that involves collaboration between various stakeholders, including government agencies, non-government organizations, community representatives and academic researchers.